SISTEM INFORMASI LAYANAN JASA LAUNDRY 57 BERBASIS WEB - Suganda, Berliana Septyani; Febriyanti, Natasya; Natanae, Juniver Christian; Pulubuhu, Andhika Rizq; Hafiiz, Muhammad Ra’afi (Jurnal Teknologi Informasi Indonesia (JTII), 2022)
The purpose of this study is to provide fast, and accurate laundry transaction information so that customers can easily obtain information about their orders just by opening the laundry website 57. Qualitative research of this type of problem solving method is PIECES. The project uses Unified Modeling Language (UML) and Object Oriented Analysis and Design (OOAD) technology. The data collection methods used are observation, interview and literature studies. Research shows that these apps can help employees' activities in terms of customer service, customers can easily see the extent of the process, and employees can easily record the results of all transactions without taking out a lot of paper. In addition, we support couriers in the delivery and delivery of customer products.